SYSTEMATIC LITERATURE REVIEW: SUSTAINABLE SILVOFISHERY DEVELOPMENT IN MANGROVE ECOSYSTEMS IN INDONESIA - rahmawaty rahmawaty; ROULINA SIMANJORANG; LIRENTA MASARI HALOHO; MARISI SIAHAAN; SURANTO (Jurnal Belantara, 2026)
Silvofishery integrates mangrove conservation with low-input aquaculture and is increasingly promoted for sustainable coastal management in Indonesia. This study aimed to identify research trends, evaluate ecological and socio-economic outcomes, synthesize factors controlling implementation success, and formulate research and policy priorities for sustainable silvofishery development in Indonesian mangrove ecosystems. A Systematic Literature Review was conducted using the PRISMA framework and complemented by descriptive bibliometric mapping with VOSviewer. The search used expanded synonyms, including silvofishery, silvo-aquaculture, integrated mangrove aquaculture, wanamina, empang parit, mangrove-based aquaculture, mangrove restoration, blue carbon, food security, climate change, and coastal communities. The Indonesia scope was applied using country-, regional-, and site-specific terms. From 200 records identified, 200 records were screened by title and abstract, 65 full-text articles were assessed for eligibility, and 10 studies published between 2010 and 2026 met the inclusion criteria for qualitative synthesis. The synthesis shows that silvofishery can improve mangrove rehabilitation, carbon stock, pond productivity, fishery resources, and coastal income, but outcomes vary across locations. Blanakan showed the strongest multi-service integration, Brebes provided the clearest long-term monitoring evidence, Banyuasin showed strong crab-silvofishery performance, and the Mahakam Delta showed high restoration relevance in a degraded landscape. Success depended on site suitability, tidal exchange, water and sediment quality, mangrove species composition, stocking intensity, institutional support, and community participation. The review concludes that silvofishery is not only an aquaculture model but also a nature-based solution that links ecosystem restoration, climate change mitigation, food security, and livelihood resilience.